2018
DOI: 10.5093/psed2018a13
|View full text |Cite
|
Sign up to set email alerts
|

El Rol de los Factores Personales y Familiares en la Autodeterminación de Jóvenes con Discapacidad Intelectual

Abstract: Financiación. Esta investigación se ha desarrollado dentro de los proyectos financiados por el Ministerio de Economía y Competitividad con la referencia PSI2015-65193-P (MINECO/ FEDER) y PSI2016-75826-P (AEI/FEDER, UE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
1
1
0
10
Order By: Relevance
“…These results strongly sustain several assumptions. First, though opportunities given at home to engage in self‐determined actions positively impact self‐determination expression, in line with a recent study held in the Spanish context (Vicente‐Sánchez et al, ), opportunities at school, as perceived by the participants, were not influencing volitional actions. Schools and colleges might thus not be providing enough opportunities for students to explore their interests and needs, either academic or not, and act accordingly.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results strongly sustain several assumptions. First, though opportunities given at home to engage in self‐determined actions positively impact self‐determination expression, in line with a recent study held in the Spanish context (Vicente‐Sánchez et al, ), opportunities at school, as perceived by the participants, were not influencing volitional actions. Schools and colleges might thus not be providing enough opportunities for students to explore their interests and needs, either academic or not, and act accordingly.…”
Section: Discussionsupporting
confidence: 79%
“…Research on people with disabilities has also reported the impact of family and educational opportunities on the development of self‐determined actions (e.g. Carter et al, ; Vicente‐Sánchez, Guillén‐Martín, Verdugo‐Alonso, & Calvo‐Álvarez, ). For example, within educational contexts, being involved in their transition and IEP planning and having opportunities for self‐determination skill development were positively correlated with later self‐determination outcomes (Morningstar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…En la revisión realizada y los diferentes artículos analizados se ha comprobado que el estudio de la autodeterminación en adolescentes diagnosticados con trastorno del espectro autista en edad escolar es un tema que ha sido poco trabajado. Sin embargo, la autodeterminación sí que ha sido una dimensión ampliamente abordada en otros contextos y con otros colectivos con capacidades y necesidades diferentes (Nota et al, 2007;Arroyave y Freyle, 2009;Arellano y Peralta, 2013;Arellano y Peralta, 2015;Vega et al, 2017;Vicente et al, 2018;Chadwick y Fullwood, 2018;Shogren et al, 2019;Taylor et al, 2019, etc.). Esta afirmación la corroboran Chou et al (2015) en su estudio sobre el análisis de la fiabilidad y validez de dos escalas para la evaluación de la autodeterminación en alumnado con TEA, añadiendo que se trata de un soporte preliminar para realizar futuros estudios con esta población, ya que anteriormente se ha realizado principalmente y en mayor medida con estudiantes con discapacidad intelectual y dificultades del aprendizaje.…”
Section: Discusión Y Conclusionesunclassified
“…En cuanto a la incidencia de factores contextuales, se ha identificado cómo el estilo de crianza (Wehmeyer et al, 2011) o la estructura familiar (Vicente, Guillén, Verdugo y Calvo, 2018) condicionan el desarrollo de la autodeterminación. Del mismo modo, las evidencias sobre la influencia de los entornos educativos formales en el desempeño de habilidades de autodeterminación sugieren que el sistema de creencias de los y las profesionales incide en su desempeño (Grigal et al, 2003).…”
unclassified